Distribution planning in design wavelength DWDM transport network - Агеев, Дмитрий Владимирович; Ковальчук, Валентина Константиновна; Переверзев, Александр Анатольевич (Eastern-European Journal of Enterprise Technologies, 2011)
The mathematical formulation of the distribution of wavelengths of light paths optic communication channels of the transport network, taking into account four-wave mixing phenomenon. Proposed method of distribution of wavelengths, which allows for nonlinear four-wave mixing phenomenon by introducing additional constraints